A new synonym, a new male description and new geographical records for three Ceraeochrysa species (Neuroptera: Chrysopidae) - Sosa, Francisco [UNESP]; De Freitas, Sergio [UNESP] (Magnolia Press, 2011)
Ceraeochrysa Adams is the largest genus in Chrysopini with 62 valid species distributed in the New World. The taxonomy of this group is complex and largely based on male genitalic characters. There are still serious complications, especially with the species that have been described solely from female specimens. The male of C. montoyana (Navás, 1913), unknown previously, is herein described for the first time, and compared with its closest relative, C. claveri (Navás, 1911). Ceraeochrysa acutipuppis Adams & Penny, 1985 is designated as a junior synonym of C. fairchildi (Banks, 1946) based on the evidence that both species share external morphological features uncommon in other species of the genus. The species C. claveri, C. fairchildi and C. montoyana are recorded from Venezuela for the first time. External morphology and genitalia of these insects are described and illustrated. © 2011 • Magnolia Press.
Keywords: Chrysopinae; Chrysopini; Green lacewing; Predator; Synonymy